A hybrid achromatic metalens - F. Balli (Nature Portfolio, 2020)
Metalenses that correct chromatic aberration also suffer from reduced focusing efficiency. Here, the authors introduce a Hybrid Achromatic Metalens which merges a metalens and phase plate to offer improved focusing efficiency over a broad wavelength range and diffraction limited imaging performance.